The First Coordination Polymers Based on 1, 3‐Diphosphaferrocenes and 1, 1′, 2, 3′, 4‐Pentaphosphaferrocenes1. Issue 5 (8th October 2015) - Heindl, Claudia; Reisinger, Sabine; Schwarzmaier, Christoph; Rummel, Lena; Virovets, Alexander V.; Peresypkina, Eugenia V.; Scheer, Manfred
Abstract: Phosphaferrocenes in combination with coinage metal salts proved to be excellent building blocks in supramolecular chemistry for the buildup of oligomeric and polymeric assemblies. The synthesis of a series of novel phosphaferrocenes containing the 1, 3‐P2 C3 i Pr3 and/or the 1, 2, 4‐P3 C2 i Pr2 ligand is described herein. The self‐assembly processes of the 1, 3‐diphospha‐, 1, 2, 4‐triphospha‐, and 1, 1′, 2, 3′, 4‐pentaphosphaferrocenes with Cu I halides led to the formation of 1D or 2D polymers. With [Cp*Fe(η 5 ‐P2 C3 i Pr3 )] (Cp* = η 5 ‐C5 Me5 ), infinite chains are formed, whereas with [(η 5 ‐P3 C2 i Pr2 )Fe(η 5 ‐P2 C3 i Pr3 )] 1D ladderlike structures are obtained. These are the first polymers containing such a di‐ and pentaphosphaferrocene, respectively. On the other hand, the use of [Cp*Fe(η 5 ‐P3 C2 i Pr2 )] leads to the construction of 2D networks with intact sandwich complexes, which is uncommon for this class of complexes. Abstract : A synthetic approach to a series of i Pr‐substituted phosphaferrocenes was found. Their self‐assembly with Cu I halides led to one‐ and two‐dimensional polymers: 1D chains containing the 1, 3‐diphosphaferrocene, 1D ladderlike structures with the 1, 1′, 2, 3′, 4‐pentaphosphaferrocene, and 2D meshlike networks bearing the 1, 2, 4‐triphosphaferrocene.